Vegetative growth and productive performance of 'Abate Fetel' and 'Rocha' pear trees on quince rootstocks - Almeida, Gustavo Klamer de; Fioravanço, João Caetano; Marodin, Gilmar Arduino Bettio (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the vegetative growth and yield of the 'Abate Fetel' and 'Rocha' pear (Pyrus communis) trees grafted onto the 'Adams', 'Ba29', and 'EMC' quince (Cydonia oblonga) rootstocks in the climatic conditions of Southern Brazil. The plants were trained on a central leader system, at a 4.0x1.0-m spacing. Vegetative growth, yield, and fruit size were evaluated. 'Rocha' showed greater vegetative growth, but also alternate bearing, mainly due to fructification problems. 'Abate Fetel' presented high flowering intensity, but a very low fructification, which limited its yield. Among rootstocks, 'Adams' induced a higher vigor during the initial stages and an increased intensity in flowering in the sixth year. In the following seasons, there was no rootstock effect on the assessed variables. 'Rocha' has a satisfactory production, whereas 'Abate Fetel' shows a weak vegetative growth and a very low production. The 'Adams', 'Ba29', and 'EMC' rootstocks induce similar vegetative and productive behavior in the 'Abate Fetel' and 'Rocha' pear trees.
Keywords: Cydonia oblonga; Pyrus communis; effective fructification